Comparative analysis of genome composition in Triticeae reveals strong variation in transposable element dynamics and nucleotide diversity. (26th November 2012) - Middleton, Christopher P.; Stein, Nils; Keller, Beat; Kilian, Benjamin; Wicker, Thomas
Summary: A 454 sequencing snapshot was utilised to investigate the genome composition and nucleotide diversity of transposable elements (TEs) for several Triticeae taxa, including Triticum aestivum, Hordeum vulgare, Hordeum spontaneum and Secale cereale together with relatives of the A, B and D genome donors of wheat, Triticum urartu (A), Aegilops speltoides (S) and Aegilops tauschii (D). Additional taxa containing the A genome, Triticum monococcum and its wild relative Triticum boeoticum, were also included. The main focus of the analysis was on the genomic composition of TEs as these make up at least 80% of the overall genome content. Although more than 200 TE families were identified in each species, approximately 50% of the overall genome comprised 12–15 TE families. The BARE1 element was the largest contributor to all genomes, contributing more than 10% to the overall genome. We also found that several TE families differ strongly in their abundance between species, indicating that TE families can thrive extremely successfully in one species while going virtually extinct in another. Additionally, the nucleotide diversity of BARE1 populations within individual genomes was measured. Interestingly, the nucleotide diversity in the domesticated barley H. vulgare cv. Barke was found to be twice as high as in its wild progenitor H. spontaneum, suggesting that the domesticated barley gained nucleotide diversity from the addition of different genotypes during the domestication and breeding process. In the rye/wheat lineage, sequence diversity of BARE1 elements was generally higher, suggesting that factors such as geographical distribution and mating systems might play a role in intragenomic TE diversity.